Feuerbach e o ateísmo antropológico - Hartmann, Paulo Airton (2012)
Feuerbach answer the question: Where and how the religion arises? The man, endowed of intelligence and consciousness, is able to think as individuals and as species. As an individual perceives limited. As a species finds its essence. His essence and all its potentials and wishes, he projects this to out of himself and call this of God. Feuerbach, with his atheism, wants repay to man the dignity lost and shows that theology is, on reality, an anthropology. Finally is made the critique of Feuerbach s critique